2017
DOI: 10.1007/s00442-017-3854-z
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring nutrients from tree leaves: effects of leaf maturity and development type on a generalist caterpillar

Abstract: The rapid growth and prolific reproduction of many insect herbivores depend on the efficiencies and rates with which they acquire nutrients from their host plants. However, little is known about how nutrient assimilation efficiencies are affected by leaf maturation or how they vary between plant species. Recent work showed that leaf maturation can greatly decrease the protein assimilation efficiency (PAE) of Lymantria dispar caterpillars on some tree species, but not on species in the willow family (Salicaceae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Previous studies reported on variations of macroelement concentrations (N, P, K, Ca, Na) in leaves of different pedunculate oak genotypes as a result of the interaction of a certain genotype and environmental factors [55]. Furthermore, foliar nutritional quality changes greatly during leaf maturation, as well as insect assimilation efficiency of compounds such as carbohydrates and proteins [56]. Along with these differences, the variability in nutrient amounts between plant species and even within a single plant (leaf maturity, for example) suggests that most insect herbivores facing heterogeneous nutritional sources regulate their nutrient intake [23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported on variations of macroelement concentrations (N, P, K, Ca, Na) in leaves of different pedunculate oak genotypes as a result of the interaction of a certain genotype and environmental factors [55]. Furthermore, foliar nutritional quality changes greatly during leaf maturation, as well as insect assimilation efficiency of compounds such as carbohydrates and proteins [56]. Along with these differences, the variability in nutrient amounts between plant species and even within a single plant (leaf maturity, for example) suggests that most insect herbivores facing heterogeneous nutritional sources regulate their nutrient intake [23].…”
Section: Discussionmentioning
confidence: 99%
“…Leaf age and traits associated with plant genotype are regarded as important determinants for the performance of plant attackers (Barbehenn et al, 2017 ; Barker et al, 2019 ; Dodd et al, 2008 ; Edwards & Ayres, 1982 ; Ekholm et al, 2017 ; Falk et al, 2018 ; Tikkanen & Julkunen‐Tiitto, 2003 ). Therefore, predicting how plant phenology responds to elevated temperatures, and how this affects resource quality for higher trophic levels, requires an understanding of how climate warming influences plant phenology throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh leaves are usually dominated by high levels of nitrogen and defensive compounds, while old leaves have a tougher surface than fresh leaves (Barton et al, 2019 ; Falk et al, 2018 ; Feeny, 1970 ; Salminen et al, 2004 ). Studies have demonstrated that leaf age can have an effect on both survival and growth rate of insect herbivores and infection by pathogens, where young leaves are usually favored (Barbehenn et al, 2017 ; Dantec et al, 2015 ; Dodd et al, 2008 ; Edwards & Ayres, 1982 ; Falk et al, 2018 ; Tikkanen & Julkunen‐Tiitto, 2003 ). From the perspective of a plant attacker, rapid changes in leaf properties can define a “window of opportunity” in spring, where leaves of a certain age are of particularly high quality to the attacker.…”
Section: Introductionmentioning
confidence: 99%
“…That eggs were typically laid on the penultimate leaves of creeping grasses may be explained by nutrition and by avoidance of natural enemies. Eggs laid on second leaves will hatch on a tender young leaf, which is probably more nutritious than both the youngest leaf and older leaves (Barbehenn et al, 2017). Furthermore, walking predators may be less likely to fi nd prey at the shoot tips of complex plants since there are many such tips, compared to other plant parts (Casas & Djemai, 2002).…”
Section: Discussionmentioning
confidence: 99%